Critical Analysis of Digital Transformation, Leadership Challenges, And Operational Success in Hospital Management - Alawi, Thabet Mohammed Taher; Alharthi, Abdulhakeem Ahmed; Alhujaily, Abdullah Saleh; Banon, Shog Solaiman; Althagafi, Sameer Aiedh; Shashah, Ashraf Ali Mohammad; AL said, Abdullah Saad; Shashah, Ayman Ali Mohammad; Alsulami, Omar Aziz Omar; Alshomrani, Muslah Break K; Aljuaid, Sultan Hajjad Owaidh (Journal of Ecohumanism, 2024)
Digital transformation has significantly impacted healthcare, particularly in hospitals, where it plays a crucial role in increasing the effectiveness of operations, delivering care to patients, and changing leaders. However, leadership challenges also emerge when new technologies are implemented in hospitals, such as resistance to change, the need for special skills, and the need to incorporate new technologies into practice. This paper aims to review the literature on the relationship between IT adoption, leadership issues, and hospital management operations. To this end, the study draws from current literature, the analysis of real-life cases, and data collected from hospital settings to establish linkages between the use of digital solutions and healthcare leadership as well as the functioning of the hospital. Takeaways from the study attributed hospital digital transformation efficiency to leadership, a change management plan, and a human factor consideration of digital technologies. Finally, this paper presents some guidelines for hospital managers and leaders regarding developing and promoting regional technologies and leadership training within their facility.